(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The image of a woman in allas is one of the most unique and profound themes of folk oral art. Allas mainly represent the colorful aspects of the life of the Turkmen people, their values, traditions, and interpersonal relationships. In particular, female images are a great source for gaining deep spiritual and social thinking through them. Each female image in allas is comprehensive, complex, and multi-layered, expressing such high qualities as human morality, kindness, loyalty, and patience. The study of these images is important for understanding popular cultural values and provides information about the role of women in challenging periods of social development.